Analisis Perbandingan KWH Meter Prabayar dan Pascabayar untuk Meningkatkan Keakuratan Pengukuran Konsumsi Listrik di PT PLN Unit Layanan Pelanggan Kota Langsa - Fachrur Rizki; Parlin Siagian; Dicky Lesmana (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This study presents a comparative analysis of prepaid and postpaid kilowatt-hour (KWH) meters in improving the accuracy of electricity consumption measurement among customers of the PT PLN Customer Service Unit (ULP) in Langsa City. The study aims to determine whether prepaid KWH meters, which require users to pay for electricity prior to consumption, provide billing and usage monitoring accuracy comparable to traditional postpaid systems, where payments are made after electricity consumption based on meter readings. The methodology used involves a detailed examination of meter readings from two different groups of consumers over a one-month period, coupled with an assessment of the impact of meter type on consumer payment behaviour and incidents of electricity theft. The results indicate significant differences in the accuracy of electricity consumption measurement between the two meter types, with prepaid meters demonstrating a potential for reducing electricity theft and improving consumer energy management through upfront payment mechanisms. In addition, the study examines the technical and psychological factors that influence consumers' energy consumption patterns, highlighting how prepaid meters can encourage more controlled and conscious use of electricity. This analysis provides valuable insights for utilities considering the implementation of prepaid systems to improve billing accuracy, reduce operating costs and promote sustainable energy consumption behaviours among consumers.